Phytoseiid mites (Acari: Phytoseiidae) of the subfamilies Phytoseiinae Berlese and Typhlodrominae Wainstein from Peru, with descriptions of two new species - Guanilo, Alberto Daniel; de Moraes, Gilberto José; Knapp, Markus (Zootaxa, 2008)
This paper reports the mites of the subfamilies Phytoseiinae and Typhlodrominae (Phytoseiidae) from Peru, providing descriptions of 2 new species, Phytoseius ortegae Guanilo and Moraes, n. sp. and Phytoseius poripherus Guanilo and Moraes, n. sp., and a taxonomic key to separate the species reported.